You are on page 1of 26

Reverse cosine rule: CosA = b + c - a/2bc

Express x-6x-7=0 as a completed square and hence solve it

1) First, write out the first bracket (x + b/2) (x - 3) 2) Multiply out the brackets and compare to the original (x - 3)(x - 3) = x - 6x + 9. You need to change the 9 into -7. So you have to minus 16 So now you have (x - 3) - 16 = o 3) Rearrange to make the squared bracket the subject (x - 3) = 16 4) Square root both sides x - 3 = 16 5) Rearrange to make x the subject and then solve x = 3 16 x = 3 + 16 x = 7 x = 3 - 16 x = -1

2x + 16x 3 1) Factorise out the 2 2(x + 8x) 3 2) Continue with the normal method 2((x + 4)-16) 3 (The negative 16 is cancel out the 2x4) 2(x + 4) - 35 (The negative 35 comes for the 2 x -16 = -32. -32 3 = -35 2(x + 4) = 35 2(x + 4) = 35 x + 4 = 35/2 x = -4 35/2

Shade the region represented by: x + y < 5, y > x +2 and y >= 1

1)

Convert each of the inequalities into an equation x + y < 5 becomes x + y = 5 and then y = -x + 5 y > x + 2 becomes y = x + 2 y >= 1 becomes y = 1

Not equal to Equal to

y-Stretch: y = kf(x) Examples: y = 3f(x), y = 2x You multiply the y coordinate by k So if its y=3f(x) then (4,3) becomes (4,9) y-Shift: y = f(x) + a Examples: y = f(x) + 3, y = sinx + 2 You add a to each y coordinate So if its y = f(x) + 4 then (4,3) becomes (4,7) x-Sretch: y = f(kx) Examples: y = f(3x), y = cos(4x) You multiply the x coordinate by the reciprocal of k So if its y = f(2x) then (4,3) becomes (2,3) x-Shift: y = f(x a) Examples: y = f(x + 4), y = 1/3(x 2) You add/subtract the opposite of a to the x coordinate So if its y = f(x 2) then (4,3) becomes (6,3) If its y = f(x + 1) then (4,3) becomes (3,3)

If you have to find the distance between 2 points on a graph, use Pythagoras. Example: 5 + 12 = 169 169 = 13

(-4,8) 13 5

(8,3)
12

Angle of Depression The angle of Depression is the angle downwards from the horizontal. The angle of Elevation is the angle upwards from the horizontal. The angle of Depression is equal to the angle of Elevation

Angle of Elevation

83 7m

Two angles + 1 side: Sine rule

53

7m

8m

Two sides + an angle NOT enclosed by them: Sine rule

53

83 Two sides + angle ENCLOSED by them: Cosine rule

7m

8m

All 3 sides + no angles: Reverse Cosine rule 8m 7m

10m

b Made 2 isosceles triangles. 2a + x = 180 2b + y = 180 x + y = 180 360 = x + y + 2(a + b) 360 = 180 + 2(a + b) 180 = 2a + 2b 90 = a + b

The line that cuts a chord directly in half (at 90 degrees) will go through the centre of the circle and therefore be the diameter

All triangles drawn from a chord will have the same angle where they touch the circle. Also, two angles on the opposite side of the chord = 180 a + b = 180

b
b

An angle made at the centre from a chord is always double the angle made at the circumference. Therefore the angle is double both of the other angles. So the other angles have to be equal

2a

a b

180 = 2a + y 180 = 2b + z 360 = y + z + x z + y = 360 - x 360 = 2(a + b) + 360 x 0 = 2(a + b) x x = 2( a + b)

z x

a + c = 180 d + b = 180 a b

d c

The angle between a tangent and a chord that meet is equal to the angle in the opposite segment

Overall force from the two tugs? 10,000N

40 Boat 20

15,000N

10,000N 40 20

Boat

15,000N

20 40

x = 10,000 + 15,000 - (2 x 10,000 x 15,000 x Cos120)


x = 21,794.49472N

120

15,000N 15,000 x Sin120 / 21,794.49472 = 36.58677555.


x a = 36.58677555 40 36.58677555 = 3.413224451

10,000N

40 B = 3.413224451 Boat

3.4